COMPARATIVE EFFECTS OF THIMALIN, EPITALAMIN, AND VILON UPON THE STATE OF IMMUNITY IN PATIENTS WITH CLINICAL COMPLICATIONS OF APPENDICITIS - B. I. Kuznik (SPb RAACI, 2014)
Abstract. It is revealed, that significant disturbances of cellular and humoral immunity are observed in patients with complicated course of appendicitis. Intramuscular administration of Thimalin (10 mg per injection), Epitalamin (10 mg per injection) for 10 days or Vilon (10 mkg per injection) during 5 or 10 days, applied as a complement to conventional treatment, proved to exert immunostimulatory effects. Moreover, it promoted healing of surgical wounds by a primary tension, and also reduced terms of the treatment by a mean of 5-6 days. To achieve similar medical effects, a twofold lesser number of Vilon single doses is required, than those of Thimalin and Epitalamin. (Med. Immunol., 2008, vol. 10, N 4-5, pp 455-462).